2003
DOI: 10.1007/s00415-003-1067-3
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic stimulation for tremorSubtle changes in episodic memory are related to stimulation per se and not to a microthalamotomy effect

Abstract: The aim of this study was to investigate the impact of unilateral deep brain stimulation (DBS) of the ventrointermediate (Vim) thalamic nucleus on neuropsychological functioning comparing stimulation-on with stimulation-off conditions. Nine patients [five patients with Parkinson's Disease (PD), two patients with essential tremor (ET) and 2 patients with multiple sclerosis (MS)] underwent comprehensive neuropsychological testing for cognitive functions, including general mental impairment, aphasia, agnosia, exe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…7,38 Interestingly, there has been a report of a subtle diminution in verbal memory in the DBS-on state versus the DBS-off state. 27 In the present study, we demonstrated that postoperative cognitive decline could be minimized by thalamic lesioning with MRgFUS. Only 5 patients manifested worsened cognitive function, but most of them (4 patients) already had cognitive impairment as a predisposing factor before surgery.…”
Section: Figsupporting
confidence: 56%
“…7,38 Interestingly, there has been a report of a subtle diminution in verbal memory in the DBS-on state versus the DBS-off state. 27 In the present study, we demonstrated that postoperative cognitive decline could be minimized by thalamic lesioning with MRgFUS. Only 5 patients manifested worsened cognitive function, but most of them (4 patients) already had cognitive impairment as a predisposing factor before surgery.…”
Section: Figsupporting
confidence: 56%
“…Four studies [9][10][11][12] have observed no widespread or significant changes in cognition, mood or behaviour after unilateral thalamic DBS, although one study suggested that statistically (but not necessarily clinically) significant declines in verbal memory are associated with left thalamic DBS. Few studies have examined mood after thalamic DBS, but one study 9 found an improvement in depressive symptoms four to 10 days after surgery.…”
Section: Thalamic Deep Brain Stimulationmentioning
confidence: 99%
“…The former have been speculated to be attributable to microlesional/oedema effects and the latter to permanent changes to neuroanatomical structures. One difference between the two studies relates to stimulation effects, which were absent in the study of Ledermann et al With thalamic DBS for ET, effects of stimulation have been postulated to account for postoperative memory [6] and verbal fluency [7] changes. Conclusions regarding stimulation effects on cognition in PSA-DBS ET patients are limited to one study at present which only analysed verbal fluency outcomes in 17 patients 3 days and 1 year after zona inserta DBS surgery [5].…”
mentioning
confidence: 93%